Differentiated Learning in Social Studies Subjects as an Effort to Create an Inclusive Learning Environment - Aprilia, Riska; Efendi, Bintang Muhammad Sahara (Proceeding International Conference on Religion, Science and Education, 2025)
Differences in student characteristics certainly affect the learning process and outcomes carried out in the classroom. Student diversity is a challenge for schools and teachers to create an inclusive learning environment. This challenge is experienced by all subject teachers, including social studies. One solution to overcome this challenge is to include a differentiated learning approach. This is urgent in the learning process in the Independent Curriculum. Therefore, this study seeks to explore the application of differentiated learning in social studies subjects in schools. The location of the study was Public JHS 4 Malang. This study used a descriptive qualitative method, with observation, direct interviews, and documentation, as well as literature studies to collect data and strengthen the research results. The results showed that social studies teachers at Public JHS 4 Malang used various media and strategies in implementing differentiated learning. Diagnostic tests were conducted before learning to determine students' abilities and needs. Analysis of the results of this test helps teachers design learning programs that are tailored to student characteristics, so that each student can develop optimally. The implementation of differentiated learning in social studies subjects at Public JHS 4 Malang has succeeded in creating a learning environment that supports student growth and motivation, making this school an ideal place to develop the individual potential of each student.